"Could you tell me what that means?": Ordinary and institutional vocabulary in police interviews with rape victims - MacLeod, Nicci J.; Hay, Elizabeth (Language and Law / Linguagem e Direito, 2025)
Perhaps the most significant outcome of the UK government’s 2021 ‘End-to-end’ review of how sexual offences are dealt with by the Criminal Justice System is Operation Soteria Bluestone (OSB), a programme of research and change which has resulted in the development of a national operating model rolled out across all 43 police forces in England and Wales in July 2023. Surprisingly, Achieving Best Evidence (ABE) interviews with victims did not form a major focus of this model, despite them being widely regarded as the most crucial link in the chain. This paper represents part of the final report on a project that aimed to begin to address this gap. The data drawn on are a set of nine ABE interviews collected from the English police force that first piloted OSB (then called Project Bluestone) but that took place during the period immediately preceding the pilot. They are thus a communicative site where potential weaknesses in investigative practice – of the type that OSB set out to tackle immediately – might be expected to be laid bare. In this paper, two issues are identified and discussed: (i) competing vocabularies and (ii) conflicting understandings of demonstrating certain concepts, e.g. lack of consent. I exemplify these conflicts as they play out in the ABE interviews, draw on the philosophical concept of hermeneutical injustice in explaining these, and conclude with some thoughts on how linguistics might usefully contribute to the new model.